Health care across the first year postpartum and experiences of women with anxiety/depressive symptoms: A longitudinal cohort of first-time mothers in Ireland (MAMMI) - Daly, Deirdre; Hannon, Susan; Higgins, Agnes (My University, 2026)
Background: Women’s increased contact with healthcare professionals during pregnancy and the early postpartum make it an opportune time to identify any physical or mental health problems that emerge during this period, yet mental health problems are under-identified in clinical settings. This study uses quantitative and qualitative survey data from a large prospective study of first-time mothers in Ireland to investigate contacts with healthcare professionals, enquiry about mental health, and women’s satisfaction with the support they received. Methods: Quantitative and qualitative data were collected during pregnancy and at 3, 6, 9 and 12 months postpartum. The sample comprised 2572 mothers reporting on postpartum anxiety/depressive symptoms using the Depression, Anxiety and Stress Scale. Results: Approximately 50–70% of women reported that a healthcare professional asked about their mental health at three months postpartum. Contact with healthcare professionals and enquiries about maternal health decreased significantly over the course of the first 12 months. Women felt that postpartum care was concluded too soon, and that appointments were often hurried and infant-focused. Women reporting anxiety/depressive symptoms had more frequent appointments for their own and their baby’s health than women who did not report symptoms. Women with symptoms were more likely to indicate they felt uncomfortable addressing sensitive topics and worried about the consequences of disclosure. Many women described positive and supportive interactions with professionals; others reported that their disclosures were dismissed, while some feared that disclosures may lead to judgment, labelling or being recommended psychotropic medication as a solution. Conclusions: The findings support the need for an expansion of the postpartum care currently provided in Ireland. Greater support for health professionals regarding asking and responding to women’s needs across the postpartum period is required to address mothers’ hesitancy to share concerns and to broaden access and pathways of care.
PUBLISHED
Keywords: Help-seeking; Perinatal mental-health; Maternal wellbeing; Healthcare systems; ANXIETY; DEPRESSION; Health outcomes; Health status and inequalities; Maternal health and maternal morbidity; Maternity Care; Mental health promotion; Midwifery; Patterns of health; Pregnancy; perinatal mental health; Mental Health/Psychosocial disability; Gender; Health